Manufacture of Graphene-based Supercapacitors - Kadhim Abdul-Rassol, Hend; Mahmoud Abdul-Hussein, Adi (Iraqi Journal of Science, 2021)
A graphene-based supercapacitors (SC) were manufactured. The main objective of this research was to use as possible as environmentally, clean and natural materials for the SC electrodes, electrolytes and the separators. The SC consisted of a multi-layer graphene (MLG); as the electrode material, prepared by mixing graphene powder with water/acetone mixture, then the solution deposited on metal foils (aluminum and copper) by chemical spray technique, which is a simple and inexpensive technique to prepare the MLG films. The spraying time was (2 and 4 minutes) for making two MLG films with different thicknesses. The electrolytes were used is (lemon juice, table salt dissolved in water, and distillated water). The separators were a commercial materials; PTFE polymer and cellulose based parchment paper (PP), as these separators are commercial their dielectric constant was calculated. The thickness of the deposited MLG, the Al and Cu foils, and the separators was measured by optical microscope. The assembled SC was tested and measured the capacitance by LCR meter, the voltage across its electrodes was measured by digital multi-meter, the structural properties were tested by X-ray diffraction (XRD) for the MLG deposited on Al and Cu foils.